Resilience, life satisfaction and forgiveness of prospective psychological counselors - Çerkez, Yağmur Çerkez (2019)
The main aim of this study is to examine resilience, life satisfaction and forgiveness levels of prospective psychological counselors. In this context, gender and number of siblings were examined for any differences. Mann-Whitney U test,  Kruskal-Wallis test, and Spearman correlation analysis were conducted. It was observed that resilience, life satisfaction, forgiveness, and forgiveness sub-dimensions were positively related. The findings revealed a significant difference in forgiveness and life satisfaction. Females had significantly higher life satisfaction, whereas males had significantly higher forgiveness levels. In terms of number of siblings, those who were single child exhibited higher levels of life satisfaction than those who have who have five or more siblings. Finally, there was a significant correlation between forgiveness, life satisfaction and resilience. The findings are discussed in the light of previous studies in the literature.